Murilo Mendes: poesia e fé / Murilo Mendes: poetry and faith - Lopes, Marcos Aparecido (PLURA, Revista de Estudos de Religião / PLURA, Journal for the Study of Religion, 2012)
O poema “Vida de Mármore”, de Murilo Mendes, contém as três categorias básicas para a sensibilidade do homem religioso: mundo, tempo e eternidade. Proponho comentar o poema com o objetivo de pensar a relação entre poesia e fé. Abstract Murilo Mendes’ poem "Vida de Mármore" (Life of Marble) contains three basic categories to the sensibility of the religious man: world, time and eternity. I propose to comment on this poem in order to think about the relationship between poetry and faith.